2016
DOI: 10.3390/su8070678
|View full text |Cite
|
Sign up to set email alerts
|

The Crowding-Out Effects of Garbage Fees and Voluntary Source Separation Programs on Waste Reduction: Evidence from China

Abstract: This paper examines how and to what degree government policies of garbage fees and voluntary source separation programs, with free indoor containers and garbage bags, can affect the effectiveness of municipal solid waste (MSW) management, in the sense of achieving a desirable reduction of per capita MSW generation. Based on city-level panel data for years 1998-2012 in China, our empirical analysis indicates that per capita MSW generated is increasing with per capita disposable income, average household size, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…In the spatial econometric model, the cross-product terms are still included in the regression analysis, and the signs of its estimation coefficients are still consistent with the traditional estimation method obtained from Table 4. Additionally, the estimated coefficient of MSW charging variable (lnFEE) is still not significantly different from zero in each spatial matrix specification, indicating that the waste pricing mechanism does not have the effect of inhibiting the PMSWG, which is consistent with the previous study [17].…”
Section: The S2sls Evaluationsupporting
confidence: 89%
See 1 more Smart Citation
“…In the spatial econometric model, the cross-product terms are still included in the regression analysis, and the signs of its estimation coefficients are still consistent with the traditional estimation method obtained from Table 4. Additionally, the estimated coefficient of MSW charging variable (lnFEE) is still not significantly different from zero in each spatial matrix specification, indicating that the waste pricing mechanism does not have the effect of inhibiting the PMSWG, which is consistent with the previous study [17].…”
Section: The S2sls Evaluationsupporting
confidence: 89%
“…In addition, as much as 1.32 to 3.52 million tons of plastic waste enters the ocean each year from China, the highest among the 20 countries assessed and more than three times as much as second-ranked Indonesia [16]. The same as other developing countries, Chinese cities are facing tremendous pressure in terms of MSWM [17]. In view of the critical situation of MSWM and the damage to the global environment and ecosystems caused by the rapid growth of MSW, China should hold the increase of MSW in check and improve the sustainability of MSWM.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Japan has set up a good image for environmental protection to the world, and China is following suit. Source separation is considered to be an effective way to reduce waste and enhance recycling in many developed countries [28]. The classified collection of garbage is the basis and guarantee of effective garbage management and recycling in Japan.…”
Section: Green Development Based On Environmental Justice and Internamentioning
confidence: 99%
“…However, the collection, disposal, and recycling of MSW cannot keep up with rapid urban development [4]. A large amount of MSW has been dumped in the areas surrounding cities, and the phenomenon of "garbage siege" is common in developing countries such as China [5][6][7]. Previous studies have demonstrated that this phenomenon stems from three main reasons.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently more than 2000 active landfills in China, but the configuration facilities of most landfills are missing, and the pollution control effect is poor [16]. Most landfills are constructed based on open dumps, which is a common pattern in developing countries [5][6][7]. The congenital deficiencies of these landfills will not only lead to the decline of urban tourism and land value [17], but will also affect the urban environment.…”
Section: Introductionmentioning
confidence: 99%